The Effect of Preparation Technology and the Complexing on the Service Properties of Self-extinguishing Copper(II) Coordinated Epoxy-amine Composites for Pouring Polymer Floors - Helen Lavrenyuk; Volodymyr-Petro Parhomenko; Borys Mykhalichko (International Journal of Technology, 2019)
Making technology of copper(II)-coordinated epoxy-amine composites with reduced combustibility has been developed that allowed to form the basis of a new type of polymer with enhanced physicochemical and mechanical properties to improve the process of pouring polymer floors. A proposed simple method allows preparing and incorporating into the epoxy resin matrix the fire retardant-hardeners. These are considered to be the interaction products of the polyethylenepolyamine (PEPA) with inorganic copper(II) salts (specifically, CuSO4, (CuOH)2CO3 and CuSiF6). The combustibility of the DGEBA/PEPA, DGEBA/PEPA-CuSO4, (DGEBA/PEPA)2-(CuOH)2CO3 and DGEBA/PEPA-CuSiF6 composites obtained (DGEBA is bisphenol A diglycidyl ether) were investigated using ceramic tube (CT) method. The flammability of the polymer samples has been evaluated using the UL94 test method according to ASTM 635–14 and ASTM D1929–16. The physical-mechanical properties were determined by considering surface hardness, tensile strength, water absorption, and chemical resistance. The effects of inorganic salts of copper(II) on the fire-hazardous indices and the performance properties of the modified epoxy-amine composites were described. The results of the CT study reveal that the maximum temperature of gases produced through combustion is appreciably decreased, along with weight loss, for modified epoxy-amine composites compared to unmodified composites. The modified polymer composites are attributed to the medium flammability substance class and can be successfully used to pour polymer floors.